The Impacts of Emergency Remote Learning in a CS Programming Course: a Case Study - Hauck, Jean C. R.; Bardini Idalino, Thaís (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2022: Anais do II Simpósio Brasileiro de Educação em Computação, 2022)
With the COVID-19 pandemic, universities had to close their campuses. The need to continue teaching in these circumstances has led to the adoption of an Emergency Remote Learning (ERL) model by many universities. Computer Science related courses needed to adapt to this model, adopting strategies and tools to keep teaching. Thus, this article presents an analysis of the impact of ERL adoption on the students’ learning outcomes in an object-oriented programming discipline. An Explanatory Case Study is carried out involving six classes, three from before and three after the ERL. The results indicate that there were no statistically significant impacts on the students’ learning outcomes, raising initial evidence that the adaptation strategies adopted may have been effective to minimize the impacts.